COMPARISON OF THE COMPLETE NUCLEOTIDE SEQUENCES OF MITOCHONDRIAL DNA FROM WISTAR AND OXYS RAT STRAINS MAINTAINED AT THE INSTITUTE OF CYTOLOGY AND GENETICS SB RAS - R. A. Maksyutov; E. V. Gavrilova; T. S. Nepomniashchikh; U. N. Rotskaya; P. S. Loshchenova; N. G. Kolosova; O. I. Sinitsyna; S. N. Shchelkunov (Вавиловский журнал генетики и селекции)
The study was performed with complete nucleotide sequences of the mitochondrial DNA of Wistar rats and prematurely aging OXYS rats, sensitive to the cataractogenic effect of galactose, kept at the Gene pool of laboratory animals shared access center, Institute of Cytology and Genetics (ICG) of the Siberian Branch of the Russian Academy of Sciences. The nucleotide sequences were submitted to GenBank. It was shown that two additional unique nucleotide substitutions between rats OXYS (ICG) and Wistar (ICG) were absent from other known nucleotide sequences of rat mitochondrial DNA of rats and that they did not cause amino acid substitutions, so that all phenotypic differences between the lines were determined only by differences in their nuclear DNA. The comparative analysis showed that Wistar (ICG) rats had a significant number of nucleotide substitutions compared to rat strains derived from an outbred Wistar colony. This observation contradicts the conjectured relationship of Wistar (ICG) rats to the original Wistar rat stock or its descendants. It is assumed that the Wistar (ICG) rats had descended from the Sprague Dawley rat line, at least, through female lineage.